Transparencia de la información en las empresas cotizantes del Ecuador. Período 2019-2020 - Basurto Alcívar, Mary Cruz (2023)
The present research work was based on analyzing the transparency of information in listed companies in Ecuador for the knowledge of the impact generated in the periods 2019-2020, in the period 2019-2020, where a methodology of three phases with their respective activities was applied. This execution consisted in determining the suitable information transparency indicators, for which a bibliographic review was carried out that allowed to know several transparency indicators used by different organizations, from which eight indicators were selected with their respective sub-indicators by means of the expert method; continuing with the development, we proceeded to know the information published by the companies before and during the pandemic, for which we had to review the web portals of the 278 entities chosen in the sample, where the dichotomous variable was used as a scoring system according to the presence or absence of information according to the indicator. In addition, a comparison was made between the period 2019 and 2020 to contrast the changes presented in that time, where a variation of 10% in access to information was evidenced, finally, an improvement plan was proposed to determine corrective actions in the listed companies in Ecuador through the application of the 5W+2H matrix. Therefore, it is concluded that the listed companies have low levels of transparency in the information they publish on their web portals, since such information is limited and does not satisfy the needs of interested parties.